Practical business math procedures - Slater, Jeffrey; Wittry, Sharon M. (McGraw-Hill/Irwin, 2014)
Provides innovative learning tools and real-world examples that will support, engage, and motivate business math students by integrating interesting real-world examples and photos from several business journals.